Molecular profiling and preclinical targeted therapeutic testing in adamantinomatous craniopharyngioma. (23rd February 2017) - Apps, John; Carreno, Gabriela; Boult, Jessica; Gutteridge, Alice; Danielson, Laura; Jani, Nital; Tossell, Kyoko; Forshew, Tim; Hargrave, Darren; Chesler, Louis; Robinson, Simon; Jacques, Thomas; et al.
Abstract: Background: Adamantinomatous craniopharyngiomas (ACP) are histologically benign but clinically aggressive tumours that lead to hypothalamic injury, visual impairment, and pituitary dysfunction. Histologically they consist of several compartments, and most cases have somatic CTNNB1 -activating mutations. Similar functional activation of CTNNB1 in the developing murine pituitary gland results in murine ACP, study of which has given insight into human ACP (eg, showing activation of paracrine sonic hedgehog [SHH] signalling). We aimed to explore the genetic and transcriptional landscape of human ACP and test the functional significance of SHH signalling in vivo. Methods: RNA sequencing and targeted next generation DNA sequencing was done in ACP samples from local and national biobanks. Weighted gene correlation network analysis (WGCNA) was used to derive modules of coexpressed genes, and results were further refined with sequencing of laser capture microdissected tissue. A preclinical vehicle (n=11) controlled trial of the SHH pathway inhibitor GDC0449 (n=12) was performed in the embryonic mouse model of ACP. Findings: Next generation sequencing of laser capture microdissected tissue confirmed heterozygous CTNNB1 mutation in all tumour compartments but not reactive tissue. WGCNA identified expression signatures of different tissue components (eg, tumour epithelium, reactive tissue, and immune infiltrate) and identified novel ACP genes (eg, BCL11B ). The tumour epithelium showed high expression of ameloblast transcription factors (eg, MSX2 ), and expression of enamel proteins ( ENAM, AMELX, AMBN ) correlated with the presence of wet keratin. RNA sequencing of laser capture microdissected tissue identified expression of SHH, transforming growth factor β1, bone morphogenic proteins, fibroblast growth factors, Wnt genes, and many cytokines and chemokines within tumour epithelial whorls and evidence of paracrine SHH signalling. Interim analysis of the GDC0449 trial suggests that inhibition of the SHH pathway might reduce survival in murine ACP (median survival 82 vs 233 days, p=0·1). Further studies showed that treatment with GDC0449 caused premature tumour induction, increased proliferation, and halved the doubling time of the solid tumour component as assessed by MRI. Interpretation: ACPs have clonal CTNNB1 mutations and share a common embryological origin with teeth. They exhibit a complex transcriptional landscape, including paracrine interactions between different cellular compartments. Studies of ACP murine models suggest that, as in pancreatic, colorectal, and bladder cancer models, caution is needed when considering the use of SHH pathway inhibitors as a treatment for human ACP. Funding: Cancer Research UK; Children with Cancer, Childhood Cancer and Leukaemia Group; Great Ormond Street Hospital Biomedical Research Centre.